A one health approach to address foodborne diseases in low‑ and middle‑income countries - Kumar, Praveen; Zhang, Wei (Ubiquity Press, Ltd., 2025)
Foodborne diseases (FBDs) are defined as any diseases that result from the ingestion of contaminated or naturally hazardous food [1]. Health outcomes due to FBDs lead to more than 100 million USD of annual preventable economic burden, and over 90% of these economic losses occur in low‑ and middle‑income countries (LMICs) [2]. FBDs disproportionately impact children under 5 years of age. Representing only 9% of the global population, they experience detrimental health outcomes including 38% of all FBD incidence and as much as 30% of premature mortality [3]. Stunting and wasting are pernicious consequences of FBDs among children under 5 years of age. Africa and South‑East Asia have the highest FBD incidence and mortality. Although 41% of the global population are poor, they account for 75% of FBD‑related premature mortality and a 72% loss in global disability‑adjusted life years (DALYs) [3]. In LMICs, FBDs arise primarily owing to the interconnected issues of dwindling animal and plant health, food systems vulnerable to contaminations, and food pathogens and zoonotic threats [1, 2, 4]. There has been a dramatic upsurge in urbanization in LMICs. This trend has accompanied dietary shifts. For example, there is an increase in consumption of animal products (the foods with the highest FBD risk) and intensively managed farming systems. Further, simple food value chains have been supplanted with complex food systems with little traceability. It is now widely acknowledged that human health is intricately linked with animal health, along with our shared ecosystem. The reduction of FBDs, thus, demands a unified framework that pays concurrent attention to the health of humans, animals, and the shared environment. This merits increased attention to adopting a One Health (OH) approach to address FBDs, and by extension, contributing to food security.